METODE VARIASI BLENDER BRANSTORMING UNTUK KETERAMPILAN MENULIS BAHASA JERMAN PESERTA DIDIK KELAS XI SEMESTER I - ULFAH, FITRIYAH (LATERNE, 2018)
Writing is the most complex skill, since it is one of the productive aspects that requires various linguistics components. German language as the foreign language has different grammar, if the grammar is compared to others, that affects to the difficulty of student’s learning process. Blender Brainstorming is one of the method that enables the students to learn writing. There are 3 steps in this method, such as individual task, partner task, and group task. The research question in this study is “how are the responses of XI grade students in 1st semester toward the Blender Brainstorming as the writing method”. The purpose of this study was to describe the response of XI grade students in 1st semester toward the Blender Brainstorming as the writing method. This study applied qualitative supported by descriptive approach, while the data were the descriptive writing test result and the questionnaire of student’s response. The result presented that the Blender Brainstorming achieved positive response. The positive response through the questionnaire and the writing test result were in mutual accord. It concluded that the Blender Brainstorming method not only showed positive response but it was also supported by the result of the writing test. Keywords: writing skill, Blender Brainstorming variation method, response